A clinico hematological correlation of autoimmune hemolytic anemia and its clinical implication - R. Goswami, Parth; B. Chaudhary, Shweta (International Journal of Medical Research and Review, 2016)
Introduction: Autoimmune hemolytic anemia characterized by production of antibodies that attach to Red cells resulting in their destruction causing anemia. AIHA could be primary or secondary to some other cause. The positive DCT is hallmark for diagnosis of AIHA. Aim of Study: To perform clinical and hematological study of AIHA and from available data to derive necessary conclusion for accurate diagnosis of AIHA. Material and Methods: The prospective study was carried out in blood bank at tertiary care hospital in positive DCT cases from suspected AIHA cases. The detail history was taken, clinical presentation studied and necessary laboratory investigations like peripheral smear examination, Reticulocyte count, Serum bilirubin, Serum LDH etc done and all data tabulated and conclusion was made for diagnosing AIHA accurately. DCT was performed both manually and using gel card technology. Conclusion: Females and age group between 20 to 30 have more predilections for developing AIHA. Secondary cases are more common and severity of presentation was aggressive in primary cases as compared to secondary. Such type of study helpful in diagnosis AIHA accurately and delay in treatment can be avoided and awareness can be created.